Urinary exosomal mRNA as a biomarker for the diagnosis of bladder cancer - Wang, Xinying; Song, Dianbin; Zhu, Baoxing; Jin, Yang; Cai, Caisen; Wang, Zhiyong (Anti-cancer drugs, 2024)
To study the diagnostic value of mRNA expression in urinary exocrine body in bladder cancer. From February 2022 to December 2022, 60 patients diagnosed with bladder cancer by pathology in the Department of Urology, Affiliated Hospital of Chengde Medical University were selected as the case group. In total, 40 healthy subjects receiving physical examinations were selected as the control group. 100 mL of morning urine samples were collected from the subjects in both groups based on the same standard. Three subjects were randomly selected from each group. Urinary exosomes were extracted by differential ultracentrifugation. High-throughput sequencing (RNA-seq) was used to detect mRNA expression profiles in urinary exosomes and identify differentially expressed genes. Bioinformatic analysis was performed to predict major biological functions of differentially expressed genes and related signaling pathways. RT-PCR validated expression levels of differentially expressed genes in urinary exosomes between the two groups. ROC curves evaluated the diagnostic value of differential genes for bladder cancer. Spearman's correlation analysis determined correlations between differentially expressed genes and the occurrence of bladder cancer. ROC curves speculated the diagnostic value of using combined differentially expressed genes. Compared with normal subjects, there were 189 significantly differentially expressed genes in urinary exosomes of bladder cancer patients, including 33 up-regulated and 156 down-regulated. According to go and kyoto encyclopedia of genes and genomes (KEGG) analysis, the above differentially expressed genes may participate in the occurrence and development of bladder cancer through the MAPK pathway, PPAP signaling pathway, PI3K Akt signaling pathway and Hippo signaling pathway, affect protein and lipid metabolism, RNase activity, polysaccharide synthesis, signal transduction and other biological processes, and participate in cell proliferation, death, movement and adhesion, as well as cell differentiation and signal transduction. RT-PCR verified that the expression of tmeff1, SDPR, ACBD7, SCG2 and COL6A2 in the two groups of samples was statistically significant ( P  < 0.05). The ROC curve showed that the area under curve area under the curve of the five differential genes were 0.6934, 0.7746, 0.7239, 0.6396 and 0.6610, respectively. The sensitivity was 42.11%, 64.86%, 47.37%, 73.53% and 76.47%, and the specificity was 90%, 81.36%, 96.36%, 61.02% and 58.18%, respectively. Spearman correlation analysis showed that tmeff1, SDPR and acbd7 were associated with the occurrence of bladder cancer. The ROC curve of the combined diagnosis of the three and the two combined diagnoses suggested that the area under the curve of the combined diagnosis of SDPR and acbd7 was 0.7945, the sensitivity was 89.09%, and the specificity was 60.53%. The gene expression profile in urinary exosomes of bladder cancer patients has changed significantly, and the differential genes may play an important biological role in the occurrence and development of bladder cancer. The combined detection of urinary exosome SDPR and ACBD7 has a certain diagnostic value for bladder cancer.